Division B commission 40: Radio astronomy - Chapman, J.; Giovaninni, G.; Taylor, R.; Carilli, C.; Hills, R.; Hirabayashi, H.; Jonas, J.; Lazio, J.; Morganti, R.; Nan, R.; Rubio, M.; Shastri, P.; et al. (2015)
© 2016 International Astronomical Union. IAU Commission 40 for Radio Astronomy (hereafter C40) brought together scientists and engineers who carry out observational and theoretical research in radio astronomy and who develop and operate the ground and space-based radio astronomy facilities and instrumentation. As of June 2015, the Commission had approximately 1,100 members from 49 countries, corresponding to nearly 10 per cent of the total IAU membership.